2021
DOI: 10.1039/d1re00098e
|View full text |Cite
|
Sign up to set email alerts
|

An automated computational approach to kinetic model discrimination and parameter estimation

Abstract: We herein report experimental applications of a novel, automated computational approach to chemical reaction network (CRN) identification. This report shows the first chemical applications of an autonomous tool to identify...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…More commonly encountered are very fast elementary reactions that occur in some processes, where it is more appropriate to describe an entire reaction with an observed rate rather than the combination of its individual elementary parts. This leads to circumstances where chemical species that are reported to have a zero-order, second-order or even noninteger-order dependence, as it is much more practical to describe the physical model in this way. …”
Section: Kinetic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…More commonly encountered are very fast elementary reactions that occur in some processes, where it is more appropriate to describe an entire reaction with an observed rate rather than the combination of its individual elementary parts. This leads to circumstances where chemical species that are reported to have a zero-order, second-order or even noninteger-order dependence, as it is much more practical to describe the physical model in this way. …”
Section: Kinetic Modelingmentioning
confidence: 99%
“…At 35 °C: blue solid triangles = experimental data, ---= kinetic fit. At 40 °C: blue solid circles = experimental data, •••••• = kinetic fit 92.…”
mentioning
confidence: 99%
“…Our group recently reported the integration of a chemical reaction network (CRN) identification tool 15 with a continuous-flow platform, every feasible reaction model was constructed and evaluated based on their respective suitability to the experimental data. 40,76 This methodology was used to determine physical model information for the formation of the cardioselective beta blocker, Metoprolol, as shown in Scheme 5. This study was found to be 24% cheaper than steady-state kinetic experiments and 106% cheaper than traditional design of experiments approaches to identify kinetic information, when considering material consumption alone.…”
Section: Tandem Experimentation and Analysismentioning
confidence: 99%
“…Building from the work of Tsu et al, 35 Bourne and coworkers created an automated RNI approach. [36][37][38] Their approach assesses full reaction profiles against all stoichiometrically feasible kinetic models to identify which fits best. It assumes a rate equation, a common assumption in kinetic model discrimination.…”
Section: Introductionmentioning
confidence: 99%